2003
DOI: 10.1093/jat/27.3.156
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR Spectroscopy and GC-MS Analysis of  -Chioralose. Application to Two Poisoning Cases

Abstract: Alpha-chloralose, a compound widely used as a rodenticide and in the control of bird pests, is readily available. Two cases of intentional poisoning are reported. Both patients became comatose and presented hypersialorrhea and myoclonal crises in the legs. They were discharged from hospital after several days. As clinical signs of alpha-chloralose poisoning lack specificity, anamnesis might be difficult, particularly in the case of delayed diagnosis. Toxicological analysis is therefore critical, and this artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 8 publications
2
11
0
3
Order By: Relevance
“…Glucuronide conjugate exceeded the free parent drug by 7.3-fold. This finding confirms that chloralose is excreted primarily as the glucuronide metabolite, as previously reported (9,16). Other analytical findings indicate the recent intake of lorazepam, chlorpromazine and mesterolone, consistent with scene investigation.…”
Section: Resultssupporting
confidence: 91%
“…Glucuronide conjugate exceeded the free parent drug by 7.3-fold. This finding confirms that chloralose is excreted primarily as the glucuronide metabolite, as previously reported (9,16). Other analytical findings indicate the recent intake of lorazepam, chlorpromazine and mesterolone, consistent with scene investigation.…”
Section: Resultssupporting
confidence: 91%
“…For the alphachloralose cases, chromatographic analysis helped to identify the cause of the poisoning. This ascertainment is found in other studies [15][16][17]. Nevertheless, the negative results is related to the kinetics of the compounds.…”
Section: Discussionsupporting
confidence: 81%
“…Diethyl ether and diethyl ether/chloroform mixtures have been used to extract residues from animal tissues or physiological fluids [6][7][8][9], however, they have the disadvantage of co-extracting a significant proportion of lipid material. In-house development of the GC-ECD method had demonstrated that acetonitrile was a suitable extractant.…”
Section: Resultsmentioning
confidence: 99%
“…Illegal baits are most frequently prepared either using the carcasses of rabbits, hares, game birds or pigeons to target predatory or scavenging animals; or using eggs, grain or bread to target other animals. Chloralose is rapidly absorbed from the gastrointestinal tract and is mainly excreted in urine, partly as the parent compound and partly as glucuronides [6,7]. Investigation of a fatal human poisoning demonstrated the presence of chloralose residues in a wide range of tissues and body fluids [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation